Herbal radiomodulators [ applications in medicine, homeland defence and space - Arora, Rajesh (CABI, 2008)
Discusses the potential of radiation countermeasure agents and radiosensitizers of herbal origin, and their multifaceted mode of action, particularly in nuclear operations, rescue operations, deep space missions, and application during radiotherapy. This book is suitable for readers in radiation biology, radiation oncology, and military medicine.